Power Relations between Tuan Guru and Sultan in the Malay World: Source of the Tuan Guru Manuscript (TGM) - Ziaulhaq Hidayat (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This article examines the power relations between Tuan Guru and the Malay Sultans. Power relations are not only in relations between people and authority but relations that support and strengthen each other’s existence. This research raises how the power relations between Tuan Guru and the Malay Sultans were formed. The Tuan Guru Manuscript (TGM) written by Tuan Guru ‘Abd al-Wahhab Rokan was used as the main source to answer the research questions. This manuscript is important because it is Tuan Guru’s letter and notes to the Sultan of Langkat. The results of this research explain that the power relations formed between Tuan Guru and the Sultans have supported the spread of the Tarekat Naqsyabandiyah-Khalidiyah Babussalam (TNKB) in the Malay world. Then, power relations have also impacted the establishment of a tarekat village. It was supported by the Sultan by providing land and other supporting facilities.